Influence of Ulnar Translation of the Radial Shaft in Distal Radius Fracture on Distal Radioulnar Joint Instability - Moritomo, Hisao; Omori, Shinsuke (Journal of Wrist Surgery, 2014)
It has been reported that the distal interosseous membrane (DIOM) of the forearm constrains the dorsal dislocation of the distal radius. A residual ulnar translation deformity of the radial shaft in distal radius fractures has the potential to cause distal radioulnar joint (DRUJ) instability when triangular fibrocartilage complex (TFCC) injury is also present, because it may result in detensioning of the DIOM. Correction of ulnar translation of the radial shaft is critical because it restores DIOM tension, which then firmly holds the ulnar head in the concavity of the sigmoid notch.
Keywords: distal oblique bundle; interosseous membrane; translation; distal radius fracture; distal radioulnar joint instability